Interventions for Inclusion in TVET through Private-Public Development Partnership in Ethiopia and Zambia - Melesse, Samson; Haley, Aimee; Wärvik, Gun-Britt (Nordic Journal of Comparative and International Education (NJCIE), 2022)
The study is about reconfiguring Technical and Vocational Education and Training (TVET) through Private-Public Development Partnership (PPDP) for the inclusion of disadvantaged groups in Ethiopia and Zambia. A PPDP is a cooperation between national and foreign actors targeted at development activities and is a governmental strategy to increase the standard of TVET, including strategies to include disadvantaged learners. This article focuses on two PPDPs, one comprising a TVET college in Ethiopia and another in Zambia. The aim is to analyse and compare the curricular strategies of these two PPDPs to revamp TVET for the inclusion of disadvantaged learners. Data was generated through document analysis, interviews and focus groups. The findings indicate that both PPDPs served as an intervention to the TVET institutions, thereby including disadvantaged learners in contexts of huge inequality of opportunities. The article points to tensions relating to inclusion, particularly about how global educational policy trends contend with the realities in local labour markets and the needs of TVET graduates who will work therein.